2012
DOI: 10.5812/jjm.3521
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Short-Term vs. Long-Term Antibiotic Therapy in Preventing Deep Infection After Orthopedic Procedures (A Prospective Observational Study)

Abstract: In using short-term antibiotic prophylaxis in clean orthopedic procedures we can avoid side effects and also it is more cost-effective. Background: Antibiotic therapy prevents postoperative infections after orthopedic procedures, but the method and prescribed dose of this therapy are debated. Short-term prophylaxis and long-term prophylaxis are 2 accepted methods after orthopedic procedures. Objectives: In this prospective observational study, we compared the results of shortterm and long-term prophylaxis afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…In our results we used cefotaxime and similar done by Kulkarni et al in India particularly Ceftriaxone and Cefotaxime preferred [14] , Similar results were found in study done by Khorrami [12,[15][16] . Various guidelines also recommends cefazolin 1gm intravenous single dose or maximum of 3 doses 8 hourly for 24 hours postoperatively as preferred antimicrobial for surgical prophylaxis of clean orthopaedic surgical procedure with implant or clean contaminated surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
“…In our results we used cefotaxime and similar done by Kulkarni et al in India particularly Ceftriaxone and Cefotaxime preferred [14] , Similar results were found in study done by Khorrami [12,[15][16] . Various guidelines also recommends cefazolin 1gm intravenous single dose or maximum of 3 doses 8 hourly for 24 hours postoperatively as preferred antimicrobial for surgical prophylaxis of clean orthopaedic surgical procedure with implant or clean contaminated surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
“…So our results are similar to study done by Kulkarni et al in India in which more than 80% of the surgeons preferred single drug as third generation cephalosporins, particularly Ceftriaxone and Cefotaxime and preferred combination of cephalosporin with aminoglycoside for all types of surgeries. [14] Similar results were found in study done by Khorrami [12,[15][16][17][18][19] A study by Patzakis reported that the combination therapy (cephalosporin + aminoglycoside) was associated with a 4.6% infection rate, whereas administration of only cephalosporin was associated with a 13% infection rate. So use of Cephalosporin with aminoglycoside in our study was justified.…”
Section: Discussionsupporting
confidence: 78%
“…Our result is nearly similar to study done by Kulkarni days) in Egypt. [9,[14][15][16]26] Though in our study prolonged prophylaxis was given, but it is not recommended. Current US guidelines recommend administration of antimicrobial prophylaxis within 120 min or 60 min of incision.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patient risk factors thought to increase the chance of SSI include advanced age, poor nutritional status, obesity, smoking, diabetes, altered immune response, length of preoperative stay, colonization with micro-organisms, coexisting infections remote from operative site, setting of the procedure (elective or emergent, clean or contaminated, and others). 13 Certain procedures are associated with low risk for a SSI, and the risks of antimicrobial prophylaxis may outweigh the benefits. Risks include allergic reactions, toxic side effects of antimicrobials, adverse interactions with other drugs, and development of resistant organisms.…”
Section: Introductionmentioning
confidence: 99%